Pengaruh Motivasi Tampil Unik Dan Sikap Terhadap Keputusan Pembelian Sepatu Sepak Bola Merek Adidas Dikota Sungai Penuh - alparedi, Topan (Innovative: Journal Of Social Science Research, 2024)
The purpose of this research is to get the real fact that there is an influence in appear uniquely motivation and manner of purchasing decision of adidas football shoes in Sungai Penuh city. For testing, the writer used 101 sample of people who have ever bought adidas football shoes in Sungai Penuh city. The choosing of sample was done by using accidental sampling method. To make the step of data exploring easier, the writer divided the variable of research into two main group, the first is independent variable that consists of the motivation of appear uniquely and consumen’s manner and the second is dependent variable that’s purchasing decision. The writer did the hypotesis testing by using inferential analysis that is through the model of multiple linear regression and t-statistics testing. According to the result of testing, the first hypothesis is rejected because it is contrary to the hypothesis and the second hypothesis is accepted. The result of this research stated that the motivation to appear uniquely and manner influence positively and significant to purchasing decision. Key word: motivation of appear uniquely, consumen’s manner, and purchasing decision